MBRS-40. HMGA2 IS A PROGNOSTIC FACTOR TO INDUCE MALIGNANT PHENOTYPE IN MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Arakawa, Yoshiki; Liu, Bin; Terada, Yukinori; Matsui, Yasuzumi; Hattori, Etsuko; Sumiyoshi, Sosuke; Fukui, Nobuyuki; Tanji, Masahiro; Mineharu, Yohei; Miyamoto, Susumu
Abstract: Medulloblastoma is the most common of the embryonal tumor arising in the cerebellum and the molecular mechanism of its oncogenesis has been revealed by recent studies. The constitutive expression of high mobility group AT-hook 2 (HMGA2) is associated with a highly malignant phenotype and reduced survival in several malignancies. However, little is known about the clinical and biological significance of HMGA2 in medulloblastoma. In this study, we explore the expression, prognostic and therapeutic role of HMGA2 in medulloblastoma. HMGA1 and HMGA2 expressions were examined using immunohistochemistry in 20 patients with medulloblastoma. To examine the function of HMGA2 expression, knock-down HMGA2 expression was applied in Daoy, D283 and D341 cells. Overexpressions of HMGA1 and HMGA2 were frequently identified in medulloblastoma tissues. In addition, high expression of HMGA2 correlated with high proliferation marker Ki-67 labeling index. High expression of HMGA2 was significantly associated with progression free survival and overall survival of patients with medulloblastoma (p=0.021 and p=0.016, respectively). Functional experiments confirmed that knock-down of HMGA2 resulted in inhibited cell proliferation, migration/invasion and enhanced apoptosis in vitro. In conclusion, HMGA2 overexpression is frequent in medulloblastoma, and its expression is related to proliferation marker and poor prognosis. These findings suggest that HMGA2 could serve as a potential target for future therapeutic strategies in medulloblastoma.